Steering the Client toward Self-sufficiency Swedish Social Workers’ Accounts of Responsibilisation - Carlsson,Daniel (2018)
In the last couple of decades in Sweden, there has been an adoption of “workfare”-oriented policy approaches to unemployment (as opposed to the former, less conditioned welfare-oriented ones). Consequently, labour market policies more and more have started to encompass the Social Services Department (in Swedish; “socialtjänsten”). In Scandinavia, active labour market policies are commonly referred to simply as “activation”; i.e., various political initiatives aimed at activating the unemployed – including social services clients – so as to swiftly render them employable. Such measures entail that social workers are expected to regularly control the activation level of clients. Moreover, new organisational models (New Public Management and Lean), have in the previous decades been embraced by the Swedish Social Services Department. The latest such, “the “Trelleborg Model”, entails that the assessment of entitlement to social assistance is undertaken by an algorithm. In the following, the purpose is to analyse how a group of social workers account for their professional life in light of all of this. From the vantage point of social constructionism and ethnomethodology, I have therefore conducted eight qualitative interviews with Swedish social workers, employed by various municipal Social Service Centres throughout the south of Sweden. I have inquired as to how they account for the day-today practices of their work as it pertains to: (1) professional functions; (2) the ways in which the said functions relate to matters of control, discipline and morality; (3) their thoughts on discretion and; (4) ideas regarding new organisational/management models (including automation initiatives such as the Trelleborg Model). I have found that the social workers define their primary task as that of steering clients toward employment and financial self-sufficiency. With regard to control, discipline and morality, they account for these matters in terms of getting clients to accept responsibility for their own livelihood; and by extension, getting them to accept certain societal norms of labour and financial self-sufficiency. As for discretion, this is a complex matter, which the social workers navigate through myriad facets of their profession (society at large, superiors, peers, legislation, professional expectations, personal feelings and so forth). Hence, making discretionary assessments is by no means a cut-and-dried matter, as one, in making such assessments, additionally ought to consider if aggravating factors to activation are at hand (e.g., family circumstances, poor education levels, immigration and integration issues and so forth). When it comes to The Trelleborg Model, it may have positive as well as negative implications, according to the participants of the study. Positive in that it may conceivably free up time, which may be devoted to the more “difficult” clients (those far from the labour market), rather than to time-consuming assessments of applications; and negative in that such models may entail an underlying view on humanity that perhaps does not have the best interests of neither social workers nor clients at heart.
Keywords: Social workers; labour market policies; activation; responsibilisation; discipline; control; discretion; street-level bureaucracy; automation